Caveolin-1 regulates the expression of tight junction proteins during hyperoxia-induced pulmonary epithelial barrier breakdown. Issue 1 (December 2016) - Xu, Shuyan; Xue, Xindong; You, Kai; Fu, Jianhua
Abstract Background Bronchopulmonary dysplasia (BPD) is a common complication in preterm infants that involves the downregulation of tight junction (TJ) proteins. However, the mechanism underlying downregulation of the expression of TJ proteins during at the early stages of hyperoxia-induced BPD remains to be understood. Here, we aimed to identify the role of caveolin-1 (Cav-1) in hyperoxia-induced pulmonary epithelial barrier breakdown. Methods First, we established an in vitro pulmonary epithelial barrier models using primary type II alveolar epithelial cells (AEC-II) from newborn rats. AEC-II was assigned to the hyperoxic (85 % O2 /5 % CO2 ) or normoxic (21 % O2 /5 % CO2 ) groups. Second, AEC-II was transfected with Cav-1-siRNA to downregulate Cav-1 under normoxic exposure. Third, AEC-II was transfected with a cDNA encoding Cav-1 to upregulate Cav-1 expression under hyperoxic exposure. Then, expression levels of Cav-1 and TJ proteins were examined by immunofluorescence staining, reverse transcription-polymerase chain reaction, and Western blotting. The TJ structures visualized using a transmission electron microscope, and transepithelial resistance and apparent permeability coefficient of fluorescein isothiocyanate–dextran, which are indicators of barrier function, were measured. Results Our data showed that exposure to hyperoxia disrupted the structure and function of the pulmonary epithelial barrier and decreased the ZO-1, occludin, claudin-4, and Cav-1 expression levels. Moreover, Cav-1 knockdown attenuated the expression of the other three genes and disrupted pulmonary epithelial barrier structure and function under normoxic exposure. However, Cav-1 upregulation markedly antagonized the hyperoxia-induced pulmonary epithelial barrier destruction and TJ protein loss. Conclusions This is the first study to present evidence illustrating the novel role of Cav-1 downregulation-mediated TJ protein loss in pulmonary epithelial barrier destruction during BPD.